Biochemical characterization of a novel haloalkane dehalogenase from a cold-adapted bacterium - Drienovska, Ivana; Chovancova, Eva; Koudelakova, Tana; Damborsky, Jiri; Chaloupkova, Radka (Applied and environmental microbiology, 2012)
A haloalkane dehalogenase, DpcA, from Psychrobacter cryohalolentis K5, representing a novel psychrophilic member of the haloalkane dehalogenase family, was identified and biochemically characterized. DpcA exhibited a unique temperature profile with exceptionally high activities at low temperatures. The psychrophilic properties of DpcA make this enzyme promising for various environmental applications.
Keywords: bakteriální proteiny; Adaptation, Physiological; koncentrace vodíkových iontů; Psychrobacter; substrátová specifita; kinetika; Hydrogen-Ion Concentration; Hydrolases; Bacterial Proteins; Kinetics; nízká teplota; fyziologická adaptace; Cold Temperature; hydrolasy; Substrate Specificity